IDENTIFIKASI KESALAHAN SISWA BERDASARKAN NEWMAN DALAM MENYELESAIKAN SOAL PADA MATERI PERSAMAAN KUADRAT TINGKAT SEKOLAH MENENGAH PERTAMA - Shella Mars Putri (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2019)
This study aims to identify student errors in working on mathematical questions in the quadratic equation material to determine the root of the quadratic equation by means of the quadratic formula (ABC formula) using the Newman analysis method. This study uses a qualitative approach and the type of research conducted is descriptive. The research subjects were taken from one class IX in SMP Negeri 54 Palembang in the 2018/2019 academic year as many as 32 students and samples taken below the KKM score were 10 students. The research instrument used the LKS test results. The data analysis concluded that students made (1) errors in the problem reading stage by 98% of students, (2) errors in understanding problems by 20% of students, (3) errors in the transformation stage by 20% students, (4) errors at the stage learning process skills for 60% of students, (5) errors at the final answer writing stage for 98% of students.